Production and economics of Gangetic mystus (Mystus cavasius) farming under different feed restriction periods in cages of floodplain ecosystem - Jesmin Ara; Md. Akhtar Hossain; Md. Abu Sayed Jewel; Md. Ayenuddin Haque (Journal of Fisheries, 2023)
High feed cost is a major problem for the promotion of a nutrient rich fish like Gangetic mystus (Mystus cavasius) in cages under floodplain ecosystem. To address this problem, production and economics of cage farming of Gangetic mystus were evaluated under different feed restriction periods in Atrai River of Chalan Beel. Four feed restriction periods were tested in floating cages under four different treatments (T1-0 day i.e., regular feeding, T2-1 day, T3-2 days, and T4-3 days feed restriction per week). Fish were fed twice daily with commercial floating pellet containing 32% protein. Water quality parameters (water temperature, dissolved oxygen, pH and ammonia-nitrogen) were within the suitable range for fish culture. Final weight, weight gain, % weight gain, average daily gain, specific growth rate and survival rate were found significantly higher at treatment T1 whereas a better feed conversion ratio was observed in T2. Significantly higher fish production and benefit were also obtained from treatment T2. The present study concluded that Gangetic mystus with a stocking density of 50 fish m–3 fed with 32% protein containing feed maintaining 1 day feeding restriction per week are economically feasible for cage culture in running water.